Antiemetic efficacy of three serotonin antagonists during high-dose chemotherapy and autologous stem cell transplantation in malignant lymphoma - Slabý, J; Trnený, M; Procházka, B; Klener, P (Neoplasma, 2000)
The aim of this study was to compare antiemetic efficacy of three serotonin antagonists, granisetron, tropisetron and ondansetron, during conditioning for autologous stem cell transplantation (ASCT). Forty-five malignant lymphoma patients (mean age 38 years, M:F 30:15), undergoing the highly emetogenic regimen BEAM prior to ASCT, were randomized to receive IV granisetron (G) 3 mg once a day, IV tropisetron (T) 5 mg once a day, or IV ondansetron (0) 8 mg twice daily, for six days. The treatment groups were comparable with respect to age, sex and previous experience of nausea and/or vomiting. Nausea and/or emesis control failure was defined as a nausea lasting > or = 4 hours and/or > or = 3 episodes of vomiting/24 h, emesis control failure as > or = 3 episodes of vomiting/24 h. Both the period of chemotherapy (6 days) and the whole period of observation (10 days) were evaluated. Nausea and/or emesis control failure occurred in 24% of patients during the period of chemotherapy and in 51% of patients throughout the whole period of observation, while emesis control failed in 2% and 27% of patients, respectively. The efficacy of three serotonin antagonists was comparable during the chemotherapy period (5 patients with nausea and/or emesis control failure in the granisetron group, 2 in the tropisetron group and 4 in the ondansetron group,p = 0.40). When evaluating the whole period of observation, the antiemetic response to G and T was significantly better than to O, nausea and/or emesis control failure having occurred in 7 (47%) patients treated with G, 5 (33%) patients treated with T, and 12 (80%) patients treated with O, p = 0.03. The results concerning emesis control failures were similar, G 4 (27%), T 1 (7%), O 7 (47%), p = 0.04. Headache was the only frequent side effect of serotonin antagonists (30% incidence). All three serotonin antagonists sufficiently controlled nausea and vomiting during high-dose chemotherapy (BEAM) administration in 67-87% of patients. In comparison with ondansetron, both tropisetron and granisetron proved to be more effective after ASCT, when emetogenic factors other than chemotherapy alone participated.
Keywords: dospělí; antiemetika; Indoles; Melphalan; Female; indoly; Tropisetron; kombinovaná terapie; karmustin; antagonisté serotoninu; Adult; ženské pohlaví; cytarabin; ondansetron; granisetron; lidé; Hematopoietic Stem Cell Transplantation; autologní transplantace; transplantace hematopoetických kmenových buněk; lymfom; Antineoplastic Combined Chemotherapy Protocols; Vomiting; Cytarabine; tropisetron; protokoly protinádorové kombinované chemoterapie; nauzea; Antiemetics; Nausea; melfalan; zvracení; etoposid; Lymphoma; Male; Combined Modality Therapy; Ondansetron; Carmustine; Granisetron; Serotonin Antagonists; mužské pohlaví; Transplantation, Autologous; Etoposide; Humans